Relationship between soil electric conductivity and satellite reflectance images in the Región de Lambayeque - Perú - Rojas Acuña, Joel (2011)
The main purpose of this work is to study the relationship between the soil electrical conductivity measured in-situ (CEe) and the satellite reflectance images of the Landsat-7 ETM sensor bands for an understanding of the spatial salinity distribution in Lambayeque. The study area was the Chacra Vieja, El Cienago fundo in the District of Lambayeque. Measurement field of CEe (dS/m) was held in the October 2007 and June 2008. The reflectance data was extracted from two satellite images taken in February 21, 2007 and February 08, 2008 from the sensor Landsat7 ETM +. Images were processed with ENVI 4.5 software and to determine the CEe of the soil samples, we used a conductivity meter, mark JENWAY 4520 and to locate the area sampling points, a GPS, Garmin was employed. The correlation coefficients (R) between the CEe in-situ and the reflectance varied from 0.062 to 0.784. The reflectance of 4 band displays the lower correlation. The best correlation model for both images occurs between the spectral reflectance of the 3 band and the CEe.